Electrophoretic analysis of the protein in the midgut of stingless bees (Apidae; Meliponinae) with a comparison of necrophagous and feeding pollen workers - Serrao, J. E.; da Cruz-Landim, C. (Assn Advan Zoology, 1998)
SDS electrophoresis of midgut proteins from two Trigonini species with different feeding habits shows many similarities and the absence of unique protein in the necrophagous stingless bee Trigona hypogea, suggesting that biochemical adaptation to necrophagy, in this bee, occurs more in the qualitative than in quantitative level. Workers of different ages display some variations in the midgut protein pattern, suggesting that it is important to know the age in studies regarding to bee digestion.